Studi Deskriptif Pengguna Secondary Account Twitter di Indonesia - Dzaki Dwitama; Fanni Putri Diana (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. High Internet usage coupled with the increasing use of social media in Indonesia is a phenomenon that needs to be understood thoroughly. Some users use multiple accounts (secondary accounts) when accessing social media. This study seeks to explain the phenomenon of Twitter secondary account usage in Indonesia. A total of 2414 samples were collected from across Indonesia. This study analyzed age, gender, number of secondary accounts used, place of residence, and motivation based on the usability and gratification paradigm. To measure motivation, the researcher used the